2006
DOI: 10.1061/(asce)0733-9399(2006)132:11(1215)
|View full text |Cite|
|
Sign up to set email alerts
|

Simulation of Crack Propagation in Asphalt Concrete Using an Intrinsic Cohesive Zone Model

Abstract: This is a practical paper which consists of investigating fracture behavior in asphalt concrete using an intrinsic cohesive zone model ͑CZM͒. The separation and traction response along the cohesive zone ahead of a crack tip is governed by an exponential cohesive law specifically tailored to describe cracking in asphalt pavement materials by means of softening associated with the cohesive law. Finite-element implementation of the CZM is accomplished by means of a user subroutine using the user element capabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(62 citation statements)
references
References 25 publications
0
61
1
Order By: Relevance
“…For instance, in the last decade XCT has been applied to characterise microstructures and properties of wide range of materials, such as geological materials (rock, soil and fossils) (Carlson, 2006), metals and alloys Marrow et al, 2006;Qian et al, 2008), porous materials (Kerckhofs et al, 2008), composites (Drummond et al, 2005;Sharma 2013), asphalt mixtures (Song et al, 2006), cement (Meyer et al, 2009) and concrete (Garboczi, 2002;Wang et al, 2003;Man and van Mier, 2008;Landis and Bolander, 2009). Many XCT studies acquire the internal structures of intact materials without external loading, or study damaged materials after loading (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in the last decade XCT has been applied to characterise microstructures and properties of wide range of materials, such as geological materials (rock, soil and fossils) (Carlson, 2006), metals and alloys Marrow et al, 2006;Qian et al, 2008), porous materials (Kerckhofs et al, 2008), composites (Drummond et al, 2005;Sharma 2013), asphalt mixtures (Song et al, 2006), cement (Meyer et al, 2009) and concrete (Garboczi, 2002;Wang et al, 2003;Man and van Mier, 2008;Landis and Bolander, 2009). Many XCT studies acquire the internal structures of intact materials without external loading, or study damaged materials after loading (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Cohesive zone models are well-established tools in classic fracture mechanics developed Fracture properties (cohesive zone parameters of asphalt and asphalt-aggregate interface) to remove stress singularities ahead of crack tips. Recently, the cohesive zone concept has been employed in several studies, most of which attempted to simulate crack-associated fracture damage of asphalt concrete mixtures (Song et al 2006;Kim et al 2007). Among the various cohesive zone models available, the present study used a cohesive zone model developed by Allen and Searcy (2001), because the model can reflect nonlinear viscoelastic damage growth in the asphalt mixtures.…”
Section: Finite-element Modeling Of Idt Fracture Testingmentioning
confidence: 99%
“…Wagoner et al (2005a) concluded in their studies that SE(B) testing is probably the most promising fracture test based on test control, crack front development, test repeatability, and mixed-mode fracture. Song et al (2006b) and used the methodology proposed by Wagoner et al (2005a) to calibrate cohesive fracture parameters used in their FEM and DEM simulations, respectively. The main problems with the use of SE(B) geometry to routinely obtain fracture properties of asphalt mixtures are that the fabrication of specimens in the laboratory becomes impractical, and that it is not often viable to extract beam specimens from mixtures in the field.…”
Section: Experimental Efforts To Characterize the Cohesive Zone Fractmentioning
confidence: 99%